1997
DOI: 10.1021/jf970293o
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Volatile Constituents in Mandarin Juices and Its Use for Comparison with Orange Juices by Multivariate Analysis

Abstract: Sixteen unpasteurized juices and one pasteurized juice from mandarin and mandarin hybrid fruit were analyzed by headspace gas chromatography (HSGC), and 42 volatile constituents were quantified in each sample. Fifteen of the mandarin juice samples had relatively low levels of volatile constituents believed important to citrus flavor when compared to comparable values in orange. The quantities were used for comparison with unpasteurized orange juices using data similarly obtained in an earlier study by HSGC. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 7 publications
3
52
3
Order By: Relevance
“…Valencene is generally associated with sweet oranges (C. sinensis), which are believed to result from an early cross between pummelo and manadarin. Some mandarin varieties have been found to contain valencene, but not nootkatone (Moshonas and Shaw, 1997); however, it is often dif®cult to determine which mandarin varieties are`true' mandarins and not hybrids. Thus, the data in the literature are inconclusive as to the evolutionary source of valencene production, but suggest that putative enzymes converting valencene to nootkatone were inherited from pummelo.…”
Section: Level Ofmentioning
confidence: 99%
“…Valencene is generally associated with sweet oranges (C. sinensis), which are believed to result from an early cross between pummelo and manadarin. Some mandarin varieties have been found to contain valencene, but not nootkatone (Moshonas and Shaw, 1997); however, it is often dif®cult to determine which mandarin varieties are`true' mandarins and not hybrids. Thus, the data in the literature are inconclusive as to the evolutionary source of valencene production, but suggest that putative enzymes converting valencene to nootkatone were inherited from pummelo.…”
Section: Level Ofmentioning
confidence: 99%
“…The extraction was typically carried out under agitation, with addition of salt (NaCl or CaCl 2 ) and a ratio (1/1) for sample/headspace volumes. Due to the occurrence of offflavors in commercial fruit juices during heat treatment and storage, the volatile composition of orange juices were well studied (Jia et al, 1998;Jordan et al, 2001;Moshonas & Shaw, 1997;Nisperos-Carriedo & Shaw, 1990;Steffen & Pawlisyn, 1996;Yang & Peppard, 1994). Conversely, only four studies described the volatiles compounds identified from mandarin juices (Dharmawan et al, 2007;Peréz et al, 2005;Pérez-López, Saura, Lorente, & Carbonell-Barachina, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…At a world scale, the knowledge about mandarin juice is almost inexistent compared with orange juice. The scarce available literature focuses on composition (Moshonas & Shaw, 1997;Trifiro et al, 1999), in detecting additions of mandarin juice to orange juice (Knight, 2000), or in comparing the effects of heat treatment conditions on the acceptability of chilled juices (Sentandreu, Carbonell, Izquierdo, & Carbonell, 2005), but little is known about the suitability of the different varieties of mandarins for juice production. A basic stage to palliate the lack of data in this field is the sensory characterization of mandarin juices.…”
Section: Introductionmentioning
confidence: 99%